2022
DOI: 10.1002/lio2.767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SNOT‐25 and ENS6Q in evaluating patients with empty nose syndrome

Abstract: Objectives: Patients with empty nose syndrome (ENS) experience paradoxical nasal obstruction and various psychological burdens. This study aimed to compare ENSspecific questionnaires of sino-nasal outcome test-25 (SNOT-25) and empty nose syndrome 6-item questionnaire (ENS6Q) in the peri-operative evaluation of ENS.Methods: This was a prospective case series study. Patients with ENS were recruited and evaluated with the SNOT-25, ENS6Q, beck depression inventory-II (BDI-II), and beck anxiety inventory (BAI) befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Our previous study revealed that the ENS6Q score had a good correlation with the BDI-II and BAI scores preoperatively, but it was not associated with postoperative BDI-II and BAI scores. Hence, a simultaneous psychological assessment is necessary when evaluating patients using the ENS6Q [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that the ENS6Q score had a good correlation with the BDI-II and BAI scores preoperatively, but it was not associated with postoperative BDI-II and BAI scores. Hence, a simultaneous psychological assessment is necessary when evaluating patients using the ENS6Q [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese versions of the Sino-Nasal Outcome Test-25 (SNOT-25) [ 15 , 20 ], Empty Nose Syndrome 6-item Questionnaire (ENS6Q) [ 12 ], Beck Depression Inventory-II (BDI-II) [ 21 ] and Beck Anxiety Inventory (BAI) [ 22 ] were used to evaluate the severity of ENS symptoms and psychological burden (depression and anxiety) in patients with ENS prior to, 6 months, and 1 year after surgery, as well as in the control group at enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted data on patient numbers, nasal symptoms, quality of life, anxiety, and depression using a standardized form 13 . The outcomes examined were changes in the SNOT, ENS6Q, anxiety, and depression scores from pre‐ to post‐procedure 14–31 . Quality assessment of randomized controlled trials was performed using the Cochrane Risk of Bias tool.…”
Section: Methodsmentioning
confidence: 99%
“…13 The outcomes examined were changes in the SNOT, ENS6Q, anxiety, and depression scores from pre-to post-procedure. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Quality assessment of randomized controlled trials was performed using the Cochrane Risk of Bias tool. Nonrandomized controlled studies were assessed employing the Newcastle-Ottawa Scale.…”
Section: Data Curation and Quality Assessmentmentioning
confidence: 99%